2020
DOI: 10.21037/gs.2019.12.11
|View full text |Cite
|
Sign up to set email alerts
|

Robotic adrenalectomy: when and how?

Abstract: Robotic compared to laparoscopic approachfeasibility and safetyScreening of literature clearly shows that RA is as feasible and as safe as LA. Unfortunately, large prospective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“… 5 Several reviews have reported rates of conversion from robotic adrenalectomy to laparoscopic and open adrenalectomy as high as 6% and 7%, respectively. 7 , 18 Conversion rates during minimally invasive adrenalectomy are higher for tumors > 6 cm in size, as removal of these large tumors can be technically challenging. However, in a single-center review by Agcaoglu et al comparing 62 patients undergoing robotic (n =24) and laparoscopic (n = 38) adrenalectomy of tumors > 5 cm, the robotic approach was associated with significantly less conversion rates, less blood loss, and a shorter hospital stay despite similar tumor sizes between these groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Several reviews have reported rates of conversion from robotic adrenalectomy to laparoscopic and open adrenalectomy as high as 6% and 7%, respectively. 7 , 18 Conversion rates during minimally invasive adrenalectomy are higher for tumors > 6 cm in size, as removal of these large tumors can be technically challenging. However, in a single-center review by Agcaoglu et al comparing 62 patients undergoing robotic (n =24) and laparoscopic (n = 38) adrenalectomy of tumors > 5 cm, the robotic approach was associated with significantly less conversion rates, less blood loss, and a shorter hospital stay despite similar tumor sizes between these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to conventional laparoscopic surgery, this technique is associated with decreased blood loss, reduced patient morbidity, and shorter hospital stay. 4 7 Over the past decade, minimally invasive surgery (MIS) departments have gained experience and familiarity with the robotic platform and expanded its utilization into adrenal surgery. Therefore, this study aims to determine the effectiveness and safety profile of transperitoneal robotic adrenalectomy in our MIS practice.…”
Section: Introductionmentioning
confidence: 99%
“…Summarized data are shown in Table 4. Discussion invasive techniques such as robotic or laparoscopic approaches have importantly increased its usage over the last 20 years since the rst description of robotic adrenalectomy (RA) [11,13,19]. In the present days, LA is considered the gold standard approach to treat adrenal masses, due to lower rates of morbidity, mortality, decreased in-hospital stay, and lower intraoperative blood loss compared with the open approach [2,[7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with open or conventional laparoscopic surgery, robot-assisted surgery potentially reduces not only contamination with body fluids and surgical gasses of the surgical area, but also the number of directly exposed medical staff [31]. This approach is well established also for endocrine surgery [32,33]. Anyway, being a doctor will never be probably the same here forward.…”
Section: The Experience Of the Endocrine Surgery Unit In An Italian Cmentioning
confidence: 99%